Names of Zero Suffixation in Russian Proverbs and Sayings - Wanjun, Chan; Korneyeva, Tatyana Alexandrovna; Markova, Tatyana Damirovna (International Journal of Criminology and Sociology, 2022)
The problem statement is to study zero exponents' text-forming function in texts of different genres and styles. The object of the study is the usual names of zero suffixation in the Russian language and the features of their functioning in the works of small folklore genres – proverbs and sayings. The purpose of the paper is to identify the main word-formation types of names of zero suffixation presented in proverbs and sayings, to evaluate their role in organizing the literary space of utterances. Leading research methods are theoretical analysis of scientific and educational literature on the topic, method of continuous sampling, language, speech and text analysis, structural and semantic analysis of language material, comparative and statistical methods, and lesson observation. The article reveals the frequency of the use of certain word-formation types of names of zero suffixation (deverbal, denominal, adjective-based) in individual proverbs and sayings, points out the frequency of unprefixed names of zero suffixation, shows the features of compatibility of deverbatives, their place in the meaningful and rhythmic construction of proverbs and sayings. The figural and expressive properties of these formations are considered. The applied significance of the study and the possibility of using the results for linguodidactic purposes of teaching Russian as a native and as a foreign language are emphasized.